Nonlinear Optical Properties of Clitoria Ternatea Dyes Using Z Scan Method - Hii, Li Ting; Adnan, Nurul Nadia Binti (Enhanced Knowledge in Sciences and Technology, 2023)
Nonlinear material has recently attracted in last decades which is very useful in optical application, but it comes with the issues of high cost, hazardous and complex synthesized methods of inorganic material. This study is aimed to determine and analyze the nonlinear absorption coefficient of the organic dye extracted from Clitoria Ternatea by using the Z-scan technique. It is measured through the open aperture of Z scan measurements to analyze the nonlinear absorption coefficient, β, on three different dye concentrations (0.004g/ml, 0.008g/ml and 0.016g/ml) at different powers. It was found that there is a decreasing trend in the value of nonlinear Absorption when the concentration increases in same power, showing that the CT dye exhibits saturable Absorption (SA). Based on these results, CT dye is a prospective competitor for building different photonics and optoelectronics equipment such as passive mode locking and Q switching of lasers due to these enticing properties.